Yasemin Yildiz. Beyond the Mother Tongue: The Postmonolingual Condition. New York: Fordham UP, 2012. 292 pp. - Suzuko M Knott (Studies in 20th & 21st Century Literature, 2015)
Review of Yasemin Yildiz. Beyond the Mother Tongue: The Postmonolingual Condition. New York: Fordham UP, 2012. 292 pp.
Keywords: postmonolingual writing; German literature; transnational writers; multilingualism